Abundance of total and metabolically active Candidatus Microthrix and fungal populations in three full-scale wastewater treatment plants. (October 2019) - Maza-Márquez, P.; Castellano-Hinojosa, A.; González-Martínez, A.; Juárez-Jiménez, B.; González-López, J.; Rodelas, B.
Abstract: The abundances of total and metabolically active populations of Candidatus Microthrix and Fungi were evaluated by quantitative PCR (qPCR) and retrotranscribed qPCR of ribosomal molecular markers in three different full-scale wastewater treatment plants (WWTPs), in absence of bulking/foaming episodes. Significant differences of the abundance of rDNAs and rRNAs of Candidatus Microthrix and Fungi were observed among the three WWTPs. The average relative abundances of 16S rDNA copies of Candidatus Microthrix to those of Bacteria ranged 3.4–8.9%. Biota-environment analysis (BIO-ENV) demonstrated that the number of copies of both 16S rDNA and rRNA of Candidatus Microthrix increased at longer hydraulic and solids' retention times and with higher nitrate concentrations in the activated sludge. The abundance of Candidatus Microthrix correlated strongly and positively with the removal efficiencies of organic matter and total nitrogen in the tested WWTPs, highlighting the role of these particular microbial group in the performance of these engineered systems. Graphical abstract: Image 1 Highlights: The abundances of Ca. Microthrix and fungi were evaluated by qPCR/RT qPCR in WWTPs. Ca. Microthrix and Fungi were numerically important fractions of the WWTPs microbiota. The relative abundance of Ca. Microthrix among total Bacteria ranged 3.4–8.9%. Ca. Microthrix abundance correlated positively with the removal of COD and total N.